Bothersome Flies: How Free-Ranging Horses Reduce Harm While Maintaining Nutrition - Rubenstein, Daniel I.; Feinstein, Lisa H. (Frontiers in Ecology and Evolution, 2021)
The horses of Shackleford Banks, NC, are harassed by many species of biting flies. Apart from being a nuisance, their bites can lead to blood loss and transmit disease. As a result, these horses tend to avoid areas where fly abundances are high. Like other free-ranging horse populations, environmental factors such as low wind speeds and high temperatures increase fly loads per horse. Similarly, coat color matters since darker horses attract more flies than lighter ones, especially on hot sunny days. Many horse populations reduce per capita fly loads by living in large groups or by bunching tightly together. Shackleford horses do so, too, but also use wind speed differences among habitats to modulate fly numbers. By adopting a systematic pattern of moving between habitats such that they only visit a habitat when wind speed is high enough to keep fly harassment to a tolerable level, they can avoid being bitten while continuing to forage. Typically, they begin the day foraging on the salt marshes where fly abundance is inherently low and are lowered further by faint early morning breezes. Later in the morning, horses move to grassy patches (swales) when increasing wind speed reduces fly landings there to levels found on the marshes. Later still, when wind speeds peak, horses begin foraging among the sand dunes. At this point wind speeds are high enough so that horses using any habitat will be minimally harassed by flies, thus enabling them to freely choose where to feed based on which habitat meets particular dietary needs for protein, energy and nutrients on any particular day. Hence, Shackleford horses follow the breeze to solve a challenging dilemma of maintaining a high nutritional plain without succumbing to fly harassment. Other free-ranging horses populations appear to have a more limited ‘either-or’ choice of 'bite or be bitten', thus limiting their decision-making options.